THE EFFECT OF PROJECT-BASED LEARNING AND PROJECT-BASED FLIPPED CLASSROOM ON CRITICAL THINKING AND CREATIVITY FOR BUSINESS ENGLISH COURSE AT HIGHER VOCATIONAL COLLEGES (Malaysian Journal of Learning and Instruction, 2024)
Purpose – With the evolving demands of the global and Chinese economies, cultivating critical thinking and creativity has become imperative for social and economic development. However, contemporary educational practices have not kept pace with thisessential need. This study examines the effects of project-based learning and project-based flipped classrooms on critical thinking and creativity in higher vocational colleges. Moreover, this research delves into the disparity and comparative analysis between the twoapproaches.Methodology – A between-group quasi-experimental study was designed. Data were collected from 120 respondents from one highervocational college in Shanxi District using cluster sampling. The Ennis-Weir Critical Thinking test and District creativity test wereused to collect data for further analysis. Data were analysed using analysis of covariance (ANCOVA) and paired-sample t-test. Pairedsample t-tests are employed to test the effects of two teaching methods, while ANCOVA is used to compare the discrepancy between the two methods. With the combination of paired sample t-test and ANCOVA, the more effective teaching method can be determined.Findings – The results indicated that project-based learning and flipped classrooms significantly affected critical thinking and creativity. Besides, the project-based flipped classrooms had a larger effect on critical thinking and creativity, proving to be a more effective teaching approach to transform the present curriculum pedagogy.Significance – This study theoretically integrates class activities into higher-order thinking skills and guides teachers and educators tocultivate talents in higher vocational education.